Marka Aureliusza filozofia życia - Błaszczyk, Marek (Człowiek i Społeczeństwo, 2023)
The article presents a critical approach to Sztuka życia według Marka Aureliusza. Rozmyślania nad „Rozmyślaniami” by Dominika Budzanowska-Weglenda (Wydawnictwo Naukowe UKSW, Warszawa 2016). It discusses the main theses presented in the dissertation and invites to reflection on the stoic philosophy of Marcus Aurelius.